A study on Consumer Reaction on Passenger Car Tyre Selection in Theni - Chitra, S.; Malarvizhi, M. (International Research Journal of Management, IT & Social Sciences, 2018)
This research investigates the consumer reaction on passenger car tyre selection in Theni. This study understanding of consumer needs and wants. Finally I have given some views and suggestions to the company with which they can satisfy the consumer.